Experimental investigation of polarisation rotation in semiconductor optical amplifiers - BRADLEY, LOUISE; Kennedy, B. F.; Philippe, S.; Landais, P.; Soto, H. (IEEE, 2004)
An experimental study of polarisation rotation in a semiconductor optical amplifier is presented. Two techniques are used to investigate the gain and birefringence along the two eigenmodes of the component waveguide, with and without injection. The first investigation is based on the residual reflectivity of the facet mirrors. From the modulation depth of polarisation resolved spectra, the gain and the refractive indices of these modes are determined. The second investigation takes into account the variation of the eigenmode gain and refractive indices as a function of injected power over the range 83.3 to 413 /spl mu/W. The results of these two experiments are compared, and it is determined that the refractive index and the single-pass gain along the horizontal axis of the waveguide are higher than those along the vertical axis. Both gain and refractive index differences increase as a function of injected power in the sample under test. Furthermore, it is concluded that polarisation rotation in this component is heavily influenced by the power dependence of the relative gain in the TE and TM modes and birefringence.
PUBLISHED
Keywords: polarisation rotation